PENERAPAN THEORY OF PLANNED BEHAVIOR DALAM MEMPREDIKSI NIAT BELI PRODUK SECOND HAND: STUDY PADA KONSUMEN IGENERATION - Purwanto, Edy; Isyanto, Isyanto (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to determine the role of theory of planned behavior in predicting consumer purchase intentions of second hand products. Methods- The object of this studyis focused on second hand clothes. Total sampel were 180 respondents who were taken through purposive sampling method. Data obtained by distributing questionnaires. Hypothesis testing used multiple regression analysis. Findings- The results of this study indicate that Attitude Toward Behavior, Subjective Norm, Perceived Behavioral Control affect consumer purchase intention. Implications-The research can confirm the accuracy of TPB in predicting purchase intention of iGeneration consumers in the context of second hand clothing. This research is also useful for second hand clothing business actors in understanding the factors that influence consumer purchase intentions of second hand clothing. Keywords: Theory of Planned Behavior, Second Hand Clothes, iGeneration